Pencegahan Iritasi Mukosa Hidung pada Pasien yang Mendapatkan Oksigen Nasal - Ninuk Dian Kurniawati; Abu Bakar (Universitas Airlangga, 2011)
Introduction: The provision of oxygen therapy is traditionally use a humidifier to moisten the oxygen and prevent irritation of the nasal mucosa. Recent research proves that the use of a maximum of 4 lpm nasal oxygen without using a humidifier (non humidifier) up to 8 hours does not cause irritation of the nasal mucosa and prevent colonization of bacteria in the humidifier. The purpose of this study was to determine the effectiveness of nasal oxygen administration using a non-humidifier more than 8 hours in the prevention of irritation of the nasal mucosa.Method: This study employed an analytic survey with cross-sectional study design. As many as 20 patients at inpatient wards of Port Health Center Hospital Surabaya were recruited as sample by means of consecutive sampling. Inclusion criteria was patients must not suffer from upper respiratory tract infection and do not suffer from impaired immunity. Independent variables were oxygen flow and long of oxygen therapy. Dependent variable was irritation of the nasal mucosa. Data were analyzed with descriptive statistics and tested with spearman rho correlation test.Result: The results showed that the use of oxygen up to 140 hours with 4 LPM had no effect on the nasal mucosa such as signs of irritation and complaints of discomfort in the nose area.Discussion: It can be concluded that the use of non-humidifier for a maximum of 140 hours with flow maximum of 4 lpm is effective in preventing irritation of the nasal mucosa. Further research on the effectiveness of non humidi fi ers in the elderly population and children under five years of age is needed.